Coupled magneto-mechanical modeling of non-linear ferromagnetic diaphragm systems. (May 2019) - Jayaneththi, V.R.; Aw, K.C.; McDaid, A.J.
Highlights: Magnetic polymer composites (MPC) are wireless soft material actuators. Nonlinear MPC diaphragm systems were modeled using magnetic body forces. Experimental analysis revealed the Kelvin magnetization force led to low model error. Abstract: Magnetic polymer composites (MPC) are shape-changing materials capable of wireless actuation. There is growing interest in MPC for biomedical and robotic applications because it removes the need for on-board power systems and electronics. Finite element (FE) methods provide a powerful platform to design and simulate MPC-driven devices. However, the accuracy of previously reported FE MPC models using magnetic body force methods is unknown given the lack of experimental validation. In this paper, a new finite element model for an MPC diaphragm actuator is proposed and experimentally validated. Here, the geometrical and electrical properties of the electromagnet were explicitly modeled. A comparative study was conducted to validate three well known magneto-mechanical coupling approaches; Maxwell stress tensor and the Kelvin magnetization force, with and without the surface force contribution. In addition, a new method for estimating the nonlinear soft-magnetic properties of MPC was also presented. Experimental validation revealed the Kelvin magnetization force with surface force contribution resulted in greater simulation accuracy. Using this method, diaphragm deflection was simulated with an RMS error of less than 0.2 mm and a mean absolute error (relative to maximum displacement) well below 10%, showing good agreement across all recorded trials. The versatility of the proposed model supports many use cases, ranging from lab-on-a-chip to implantable drug delivery. The generalizable nature of this work also provides the potential for translation to other deformation modes and MPC actuator configurations.